2002
DOI: 10.1001/archinte.162.11.1293
|View full text |Cite
|
Sign up to set email alerts
|

Cevimeline for the Treatment of Xerostomia in Patients With Sjögren Syndrome

Abstract: Therapy with cevimeline, 30 mg 3 times daily, seems to be well tolerated and to provide substantive relief of xerostomia symptoms. Although both dosages of cevimeline provided symptomatic improvement, 60 mg 3 times daily was associated with an increase in the occurrence of adverse events, particularly gastrointestinal tract disorders. Use of 30 mg of cevimeline provides a new option for the treatment of xerostomia in Sjögren syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
0
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(91 citation statements)
references
References 7 publications
3
82
0
5
Order By: Relevance
“…Therefore, for early diagnosis requiring high sensitivity of a test, additional SGUS markers or other tests have to be identified and included. Given the availability of effective symptomatic therapies, such as pilocarpine or cevimeline (17,18), or the possibility of stopping disease progress with early aggressive biologic therapy (19), our score should not be applied for selection of patients for early treatment approaches. There was, however, no relationship between age or disease duration and SGUS score, but the number of included very early primary SS patients was low.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, for early diagnosis requiring high sensitivity of a test, additional SGUS markers or other tests have to be identified and included. Given the availability of effective symptomatic therapies, such as pilocarpine or cevimeline (17,18), or the possibility of stopping disease progress with early aggressive biologic therapy (19), our score should not be applied for selection of patients for early treatment approaches. There was, however, no relationship between age or disease duration and SGUS score, but the number of included very early primary SS patients was low.…”
Section: Discussionmentioning
confidence: 99%
“…Oral doses of cevimeline hydrochloride hydrate significantly improved subjective symptoms of dry mouth and dry eyes, and increased salivary flow 3) . However, adverse effects were frequently reported, such as nausea and abdominal pain.…”
Section: Discussionmentioning
confidence: 92%
“…In animal studies, cevimeline doses sufficient to induce salivation generally did not affect the central nervous system (oral administration of 3-10 mg/kg), general behavior, cardiovascular, respiratory, gastrointestinal, or urinary systems [1,3]. In human studies, while headache, dizziness, and nervousness were reported as adverse central nervous system events, they were not significantly different between the 60 mg three times daily (tid) patient group as compared to the placebo [4].…”
Section: Discussionmentioning
confidence: 96%